Strategic plan - International Livestock Research Institute (International Livestock Research Institute, 1996)
This strategic plan for the International Livestock Research Institute (ILRI) was developed through an intensive process involving consultation with stakeholders inside and outside the Consultative Group for International Agricultural Research (CGIAR). The plan takes into account the broader requirements for livestock research in support of ILRI, these are stated in the context of the broader priorities for international livestock research involving other institutions around the world. Pricipal steps in the process of developing the strategic plan are listed. The strategic plan has served as the basis for a unified strategy for livestock research in the CGIAR and for development of the medium-term plans for ILRI programmes. This document is divided in four parts. The first part, the context, looks into the livestock sector, guiding principles and developing the strategy. The second part, a unified strategy for CGIAR livestock research highlights CGIAR vision and strategy over the next decades, mandate and objectives, CGIAR resources for livestock research, and global and ecoregional priorities in livestock research. Topics of discussion under the third part, defining the programme, include comparative advantage; animal health; genetics; nutrition; feed resources; farming systems; natural resources; policy, economics, social sciences, non-ruminant meat production, institution building, and wider horizons. The consequent research requirements for the three regions outside Africa, viz, ASIA, LAC, WANA, is also presented. The last part implementing the strategy examines the present balance of livestock research, managing the unified strategy, cooperative links with NARS; scientific consortia, competitive contracts and looks into what is new in the strategic plan.